Innovations in mandibular advancement splint therapy for obstructive sleep apnoea - Mohammadieh, Anna; Tong, Benjamin; De Chazal, Philip; Cistulli, Peter A. (Frontiers in Sleep, 2023)
1 Introduction Mandibular advancement splint (MAS) therapy emerged as an effective therapy for obstructive sleep apnoea (OSA) in the mid 1990s (Ferguson et al., 1996, Clark et al., 1996), and is now the leading treatment alternative for OSA (Ramar et al., 2015). Since its inception, the field has seen a suite of revisions and advances in relation to design and customisation, fabrication, titration methods, response prediction models and the integration of data collection technology. This paper reviews these current and emerging innovations in MAS therapy and their impact upon sleep apnoea management.